Women’s satisfaction with intrapartum care and its predictors at Harar hospitals, Eastern Ethiopia: a cross-sectional study - Getenet AB; Teji Roba K; Seyoum Endale B; Mersha Mamo A; Darghawth R (Dove Medical Press, 2018)
Agegnehu Bante Getenet,1 Kedir Teji Roba,2 Berhanu Seyoum Endale,3 Abera Mersha Mamo,1 Rasha Darghawth4 1Department of Nursing, College of Medicine and Health Sciences, Arba Minch University, Arba Minch, Ethiopia; 2Department of Public Health, School of Nursing and Midwifery, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 3Department of Medical Laboratory Sciences, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 4Business Development Officer with CARE Ethiopia and Cuso International, Monitoring and Evaluation Advisor, Harar, Ethiopia Background: Satisfaction with intrapartum care is crucial for the well-being of the mother and newborn. It also serves as a proxy indicator for future utilization and recommendation of the facility. Conversely, little is known about women’s level of satisfaction during the intrapartum period in the Ethiopian context of a high maternal mortality ratio. As such, the aim of this study was to assess women’s satisfaction with intrapartum care and its predictors at hospitals in Harar, Eastern Ethiopia. Materials and methods: A hospital-based, analytical, cross-sectional study was conducted in Harar hospitals, Eastern Ethiopia from February 1 to 28, 2017. The data were collected using an interviewer-administered questioner from 398 women who delivered in the selected hospitals during the data collection period. The collected data were entered into EpiData version 3.1 and analyzed using SPSS version 22.0. Bivariate and multivariable logistic regression was applied to identify the effect of each predictor on the outcome variable (satisfaction). A P-value of <0.05 was considered to be statistically significant. Results: The proportion of women who were satisfied with intrapartum care in this study was 84.7% (95% CI: 81.1, 88.2). Factors including a minimal waiting time to be seen by the healthcare provider, ample availability of emergency drugs within the hospital, not having antenatal care follow-up, having a previous experience of home delivery, planning to deliver in the hospital, and experiencing a short hospital stay after delivery were statistically and positively associated with women’s satisfaction. Conclusion: Overall, ~85% of the women were satisfied with the service provided in the facilities. Decreasing waiting time to be seen by the healthcare providers, ensuring emergency drugs in the hospitals, advising mothers to have antenatal care follow-up, and delivering in the health facilities are crucial to improve the quality of intrapartum care. Keywords: satisfaction, intrapartum care, labor, hospitals, Ethiopia, delivery care, predictor